Pengaruh Profitabilitas, Leverage dan Likuiditas Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Makan dan Minuman yang Terdaftar di BEI 2021-2023 - Riski Kurniawan; Emilia Gustini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to obtain empirical evidence and analyze the influence of profitability, leverage and liquidity on company value. Type The research used is a quantitative approach. The population of this study is a Food and Beverage Sub Sector Company that listed on the Indonesian Stock Exchange for the 2021-2023 period. Sampling technique used purposive sampling technique to obtain 90 reports financial results obtained from a sample of 30 companies over a three year period. Hypothesis testing was carried out using multiple regression analysis using SPSS version 26 with a significance value set at 5%. The results of this research show that the variables are profitability, leverage and liquidity has a significant effect on company value.